POLA HUKUMAN TERPIDANA ANAK DAN KORUPTOR BERDASARKAN KEDAULATAN TUHAN, RAKYAT, HUKUM - Manuasa Saragi (Fakultas Hukum Universitas Kristen Indonesia, 2016)
Policy about program on legal development still need making. Attempt to realize national legal system should continue, that is in according to Annex of Legislation Number 17 Year 2007 includes development of legal substances; completing of legal structure, etc. For reaching aim entangles whole sosial component that has huge legal awareness for supporting realisation of system to be hoped. Making for attainment the ideal implies developing of substances, and improving of holding. Criminal law role is to control the public order and to directing of individual suit to general rule. Quality of enforcer/ing need accurateness, I assess any lack of our legal system for attaining the more civilized regulation. The research focusing, that penal system of Indonesia‟s law lack in corelating of punishing to juvenile and corruptor in dimension of nation development. The juvenile must not obstructed toward aim of national development, and corrupting must as far as possible evaded so that not creating failure to state in serving majorite if not whole people. Two main actors of the nation journey need to be treated with special penal that encertain nation existence. My research to the problem, is normatif in kind, it result in prediction that corelating of pattern of punishing to nation development agenda promises safety of nation.Kata Kunci: Pola Hukuman Terpidana